Something more about the essay. The essay in Spain (2001-2002) (XXI Century. Spanish Literature and Culture, 2003)
This work analyzes the Spanish essay’s most important contributions of 2001 and 2002. The thematic variety of the essay is evident. The essays achieved provide a balance between high-minded thought and lighthearted entertainment. The article pays special attention to the most important philosophical essays.
Keywords: Essay; Philosophy